Overtime risk preference and its determinants: Evidence from Indonesia - Muhammad Yusuf Indra Purnama; Linggar Ikhsan Nugroho (Universitas Sebelas Maret, 2020)
This research aims at examining the potential determinants of overtime risk preference in Indonesia–one of the most diverse countries in the world. We used household and individual data as well, taken from the fourth and fifth wave of the Indonesia Family Life Survey (IFLS). The risk aversion of the individual was observed and elicited using hypothetical gambling questions. From the result of Ordinary Least Square (OLS) estimation, we find preliminary evidence that there is a decrease in risk-aversion among individuals over time. However, there is little evidence that catastrophe will alter risk choice as a proxy for a significant life event. Furthermore, our empirical finding also revealed that risk tolerance is motivated not only by demographic factors but also by the education level and individual’s time preference.